Genesis as dialogue: a literary, historical, & theological commentary - Brodie, Thomas L. (Oxford University Press, 2001)
Recent years have seen a remarkable surge in interest in the book of Genesis - the first book of the Bible. This text aims to offer a complete and accessible overview of Genesis, from literary, theological, and historical standpoints